The Effect of Welding Residual Stress for Making Artificial Stress Corrosion Crack in the STS 304 Pipe - Jae-Seong Kim; Bo-Young Lee; Woong-Gi Hwang; Sung-Sik Kang (Advances in Materials Science and Engineering)
The stress corrosion crack is one of the fracture phenomena for the major structure components in nuclear power plant. During the operation of a power plant, stress corrosion cracks are initiated and grown especially in dissimilar weldment of primary loop components. In particular, stress corrosion crack usually occurs when the following three factors exist at the same time: susceptible material, corrosive environment, and tensile stress (residual stress included). Thus, residual stress becomes a critical factor for stress corrosion crack when it is difficult to improve the material corrosivity of the components and their environment under operating conditions. In this study, stress corrosion cracks were artificially produced on STS 304 pipe itself by control of welding residual stress. We used the instrumented indentation technique and 3D FEM analysis (using ANSYS 12) to evaluate the residual stress values in the GTAW area. We used the custom-made device for fabricating the stress corrosion crack in the inner STS 304 pipe wall. As the result of both FEM analysis and experiment, the stress corrosion crack was quickly generated and could be reproduced, and it could be controlled by welding residual stress.